PERBEDAAN KARAKTERISTIK MARSHALL CAMPURAN AC-BC BERGRADASI HALUS DENGAN CAMPURAN AC-BC BERGRADASI KASAR - Zeinvonda Ihza Yudho Bramantio; Nurani Hartatik (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Pavement layers in Indonesia have started to use hot mixes for resurfacing, maintenance, improvement, and construction of new roads. One type of hot mix asphalt that is often used is Asphalt Concrete (Laston) or AC (Asphalt Concrete). One type of asphalt pavement in this specification is asphalt concrete (Laston) or better known as AC (Asphalt Concrete). Laston is more resistant to plastic melting but quite sensitive to cracking. The general type of damage experienced by the Laston mixture is cracking and/or grain detachment. By using the 2010 road pavement general specifications guide, the general problem encountered is how the difference in presentation of the optimum bitumen content is used for coarse and fine graded materials on the AC-BC layer. what I did was to find out the differences in Marshall characteristics using finely graded AC-BC and coarse-graded AC-BC. The optimum bitumen content in the finely graded AC-BC mixture obtained a value of 5.125%, while the coarse-graded AC-BC mixture obtained a value of 4.575%.